2021
DOI: 10.7759/cureus.19277
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Critical Shoulder Angle in Secondary Rotator Cuff Failure After Shoulder Replacement: An Age- and Sex-Matched Case-Control Study

Abstract: Introduction Decreased or increased critical shoulder angles (CSA) are associated with osteoarthritis or rotator cuff failure respectively. Secondary cuff failure after shoulder arthroplasty is disabling and often requires additional surgery. The aim of this study was to investigate if the initial CSA correlated with cuff failure in the context of shoulder arthroplasty. Methods Patients from a tertiary referral centre were reviewed from 2011-2017. Those who underwent revision f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…This finding was also demonstrated by Daggett et al 29 , where a high CSA was seen in patients with massive cuff tears. Filer et al 30 also found greater preoperative CSA values in those requiring revision for cuff deficiency in a matched case series of 16 patients undergoing revision surgery for failed hemiarthroplasty or TSA.…”
Section: Risk Factorsmentioning
confidence: 86%
“…This finding was also demonstrated by Daggett et al 29 , where a high CSA was seen in patients with massive cuff tears. Filer et al 30 also found greater preoperative CSA values in those requiring revision for cuff deficiency in a matched case series of 16 patients undergoing revision surgery for failed hemiarthroplasty or TSA.…”
Section: Risk Factorsmentioning
confidence: 86%